Inhibitive effect of Chlorophytum borivilianum root extract on mild steel corrosion in HCl and H2SO4 solutions - Ji G.; Dwivedi P.; Sundaram S.; Prakash R. (My University, 2025)
Inhibition effect of Chlorophytum borivilianum root extract (CBRE) on mild steel corrosion in 1 M HCl and 0.5 M H2SO4 media has been studied using various techniques, viz., weight loss, electrochemical impedance spectroscopy, Tafel polarization, and scanning electron microscopy. Results indicate that inhibition efficiency of CBRE increases with an increase in inhibitor concentration in both acid media. Furthermore, the effect of immersion time (120 h), temperature (35-55 C), and acid concentration on the inhibition potential of CBRE has been investigated by weight loss method. Characterization of CBRE is carried out using Fourier transform infrared spectroscopy, UV-visible spectroscopy, and preliminary phytochemical screening tests. The Langmuir isotherm model is proposed as the most suitable adsorption isotherm in both acid solutions. UV-visible study and scanning electron microscopy images have confirmed the molecular adsorption of the extract on a mild steel surface. Results of the techniques used are in good agreement and reflect the potential of the extract for corrosion inhibition of mild steel in acidic environments. © 2013 American Chemical Society.